Poligami dalam Padangan Quraish Shihab dan Sayyid Qutb - Firman Doni; Risman Bustamam (IAIN Batusangkar, 2021)
An understanding of the interpretation of the polygamy verse that is less in-depth has resulted in many misunderstandings and is considered controversial in the general public. The aims of this study are: (1) To find out the law of polygamy according to Quraish Shihab and Sayyid Qutb, (2) To find out the concept of fairness in polygamy, (3) To find out apart from the concept of fairness in emergency conditions that allow polygamy. including the type of library research (library research) with the thematic interpretation analysis method or maudhu'i and comparison method or muqarran. The results of this study are: 1) According to Quraish Shihab, polygamy is like an emergency exit, according to Sayyid Qutb. 2) According to Quraish Shihab, justice which is material is not immaterial. according to Sayyid Qutb, justice in muamalah, livelihood, association and relationships. 3) Emergency conditions that allow polygamy, according to Quraish Shihab, are fewer men than women, war, infertility. According to Sayyid Qutb, the number of women exceeds the number of men, the fertility period of men is longer than that of women.